Bibliometric Analysis: Research on Batik in International Publications - Denny Sukma Eka Atmaja; Herianto Herianto; Muhammad Kusumawan Herliansyah; Andi Sudiarso (International Journal of Innovation in Enterprise System, 2023)
Batik is an Indonesian cultural tradition that carries profound philosophical meanings embedded in its patterns and high artistic value. This is evident from its early origins when batik was used within a very limited keraton environment. Now it has become a commodity of the Indonesian creative industry that has ventured into the global market. This paper addresses the following issues: the annual number of international scholarly publications in the field of batik to be published in Scopus, the productivity of researchers working in the field of batik, and the methodology for using keywords to map the development of international research publications on batik. Based on the discussion and simulation using VOSviewer software, it can be concluded that the development and growth, especially in the field of batik, from 2012 – 2022, indexed in Scopus, reached 213 publications (18.73%) in 2020. The majority of publications in the field of batik were published in the IOP Conference Series: Earth and Environmental Science. Diponegoro University is the institution that has published the most research in the field of batik, and Indonesia is one of the countries with the highest contributors. The researcher with high productivity in the field of batik is Widiaty, I, with a total of 15 publications from 2012 to 2022, specifically in the field of batik. Regarding the development map of the field of batik based on co-word analysis, there are 7 clusters, where new research topics are identified that can still be further developed, especially in the field of batik.